ARK 1999 : AWI airborne Radio-Echo Sounding Data over Northeast Greenland between North GRIP, GRIP, and GISP2 ice core sites (NOGRAM project), Version 2 - Heinrich Miller; Daniel Steinhage; Uwe F Meyer; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system (Nixdorf et al., 1999) during the Arctic season of 1999. The profiles extend across the Northeast Greenland Ice Sheet betweenNorth GRIP, GRIP, and GISP2 ice core sites. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.